2007
DOI: 10.1038/sj.onc.1210825
|View full text |Cite
|
Sign up to set email alerts
|

Molecular effectors and modulators of hypericin-mediated cell death in bladder cancer cells

Abstract: Photodynamic therapy (PDT) is an anticancer approach utilizing a light-absorbing molecule and visible light irradiation to generate, in the presence of O 2 , cytotoxic reactive oxygen species, which cause tumor ablation. Given that the photosensitizer hypericin is under consideration for PDT treatment of bladder cancer we used oligonucleotide microarrays in the T24 bladder cancer cell line to identify differentially expressed genes with therapeutic potential. This study reveals that the expression of several g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(94 citation statements)
references
References 53 publications
6
86
2
Order By: Relevance
“…P38 is also a stress induced kinase (Zarubin & Han 2005) shown to be activated after PDT with different photosensitizers. PDT-induced p38 activation has been reported as a death mechanism as well as a rescuing signal and the impact of p38 signalling on cell death after PDT seems to depend on both the photosensitizer, PDT-dose and the cell line (Klotz et al 1999, Assefa et al 1999, Xue et al 1999, Zhuang et al 2000, Tong et al 2003, Kralova et al 2007, Buytaert et al 2008. Activation of p38 was observed 5 min after LD 50 TPPS 2a -PDT in all investigated cell lines (NuTu-19, WiDr and A-431) (paper IV and VI).…”
Section: The Impact Of Mapk Signallingmentioning
confidence: 80%
“…P38 is also a stress induced kinase (Zarubin & Han 2005) shown to be activated after PDT with different photosensitizers. PDT-induced p38 activation has been reported as a death mechanism as well as a rescuing signal and the impact of p38 signalling on cell death after PDT seems to depend on both the photosensitizer, PDT-dose and the cell line (Klotz et al 1999, Assefa et al 1999, Xue et al 1999, Zhuang et al 2000, Tong et al 2003, Kralova et al 2007, Buytaert et al 2008. Activation of p38 was observed 5 min after LD 50 TPPS 2a -PDT in all investigated cell lines (NuTu-19, WiDr and A-431) (paper IV and VI).…”
Section: The Impact Of Mapk Signallingmentioning
confidence: 80%
“…9,22,23 Phox-ER stress is characterized by the activation of the EIF2AK3-EIF2A-ATF4 branch (EIF2AK3: eukaryotic translation initiation factor 2-alpha kinase 3, also called PKR-like ER kinase; EIF2A: eukaryotic translation initiation factor 2A; and ATF4: activating transcription factor 4) and ERN1-XBP1 branch (ERN1: endoplasmic reticulum to nucleus signaling 1, also called inositol-requiring enzyme 1; XBP1: X-box binding protein 1) of the unfolded protein response; 24 and ultimately culminates into BAX (BCL2-associated X protein) and BAK1 (BCL2-antagonist/killer 1)-dependent mitochondrial apoptosis. 22,23,25 Hyp-PDT-induced ICD 8,16,17 consists of the concomitant preapoptotic emission (30 to 60 min post-PDT, before phosphatidylserine externalization) 9,17 of ATP and CALR through an overlapping molecular trail primarily governed by ROS production, the ER stressassociated kinase EIF2AK3, ER-to-Golgi anterograde transport and class I phosphoinositide-3-kinase (phosphatidylinositol-4,5-bisphosphate 3-kinase, catalytic subunit alpha/PIK3CA) activity. 8,9,17 This is followed by late apoptotic (passive) release of chaperones like HSPA1A/HSP70 and HSP90AA1/HSP90.…”
Section: Introductionmentioning
confidence: 99%
“…dependent or -independent pathways on one hand, but also activation of survival pathways via p38 MAPK on the other hand (10). Previous studies of our group showed that hypericin-PDT on A-431 cells induced preferentially apoptosis, executed via the mitochondrial pathway activating the caspases 9, 6 and 3, but also caspase 2 of the receptor-mediated pathway, maybe in a feedback loop (11).…”
Section: Time-resolved Gene Expression Profiling Of Human Squamous Cementioning
confidence: 99%